Silane-Based SAMs Deposited by Spin Coating as a Versatile Alternative Process to Solution Immersion - Rouvière, Lisa (Langmuir : the ACS journal of surfaces and colloids, 2022)
Functionalization of silica surfaces with silane-based self-assembled monolayers (SAMs) is widely used in material sciences to tune surface properties and introduce terminal functional groups enabling subsequent chemical surface reactions and immobilization of (bio)molecules. Here, we report on the synthesis of four organotrimethoxysilanes with various molecular structures and we compare their grafting by spin coating with the one performed by the conventional solution immersion method. Strikingly, this study clearly demonstrates that the spin coating technique is a versatile, fast, and more convenient alternative process to prepare robust, smooth, and homogeneous SAMs with similar properties and quality as those deposited via immersion. SAMs were characterized by PM-IRRAS, AFM, and wettability measurements. SAMs can undergo several chemical surface modifications, and the reactivity of amine-terminated SAM was confirmed by PM-IRRAS and fluorescence measurements